2006
DOI: 10.1007/s10295-006-0095-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrate treatment on a mixed species, oil field microbial biofilm

Abstract: Biofilms of bacteria, indigenous to oil field produced water, were grown in square section, glass capillary flow cells at 45 degrees C. Initially, in situ image analysis microscopy revealed predominantly coccoid bacteria (length-to-width ratio measurements (l (c):w (c)) of bacterial cells gave a mean value of 1.1), while chemical measurements confirmed sulphate reduction and sulphide production. After nitrate ion addition at 100 and 80 mg/l, in the two repeat experiments respectively, the dominance of rod-shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…In addition to microbiologically influenced corrosion and reservoir souring, the efficiency of oil production is decreased due to plugging by SRP biomass and precipitated metal sulfides (12,39). Besides the use of broadspectrum biocides or inhibitors for sulfate reduction, the addition of nitrate effectively decreased the net production of H 2 S in model column studies (15,20,38) and field trials (7,53). The mechanisms by which nitrate addition might affect souring control are (i) the stimulation of heterotrophic nitrate-reducing bacteria (hNRB) that outcompete SRP for electron donors, (ii) the activity of nitrate-reducing, sulfide-oxidizing bacteria (NR-SOB), and (iii) the inhibition of SRP by the production of nitrite and nitrous oxides (21,51).…”
mentioning
confidence: 99%
“…In addition to microbiologically influenced corrosion and reservoir souring, the efficiency of oil production is decreased due to plugging by SRP biomass and precipitated metal sulfides (12,39). Besides the use of broadspectrum biocides or inhibitors for sulfate reduction, the addition of nitrate effectively decreased the net production of H 2 S in model column studies (15,20,38) and field trials (7,53). The mechanisms by which nitrate addition might affect souring control are (i) the stimulation of heterotrophic nitrate-reducing bacteria (hNRB) that outcompete SRP for electron donors, (ii) the activity of nitrate-reducing, sulfide-oxidizing bacteria (NR-SOB), and (iii) the inhibition of SRP by the production of nitrite and nitrous oxides (21,51).…”
mentioning
confidence: 99%
“…Para as respostas Y1 e Y2, correspondentes aos tempos de incubação de 7 e 14 dias, respectivamente, observa-se que o modelo matemático foi altamente significativo, conseguindo explicar 99,6 e 93,6% da variação total em torno da média, sendo os valores de F calculado (184,78 e 11,72) maiores que os valores de F crítico (6,26 (19,0). Sendo assim, pode-se aferir que para o tempo de incubação de 28 dias, o modelo não se ajustou bem aos dados.…”
Section: Resultsunclassified
“…As células microbianas sésseis encontram-se imersas em uma matriz exopolimérica que pode dificultar a difusão do nitrato. 19 de ácido ascórbico como agente redutor, a fim de se estabelecer condição de anaerobiose. Todos os componentes foram solubilizados em água produzida e o pH do meio ajustado em 7,0 ± 0,5 com adição de NaOH 1,0 mol L -1 .…”
Section: Introductionunclassified
“…Previous studies have found that the Marinobacter group is of significance for nitrate assimilation and is positively correlated to nitrate concentration [9]. Marinobacter strains have been applied to successfully treat reservoir souring [20]. Marinobacter associated with Alteromonadales were abundant in the water column, indicating an important role in nitrate assimilation in the Indian Ocean.…”
Section: Vertical Distribution Of Nab In the Indian Oceanmentioning
confidence: 97%